2020
DOI: 10.1108/bfj-07-2020-0593
|View full text |Cite
|
Sign up to set email alerts
|

“My little piece of the planet”: the multiplicity of well-being benefits from allotment gardening

Abstract: PurposeParticipation in urban horticulture (UH) is increasing in popularity, and evidence is emerging about the wide range of social and environmental benefits “grow your own” can also provide. UH can increase mental and physical well-being, as well as improve nature connectedness, social capital and community cohesion.Design/methodology/approachThis study focusses on allotments, which is one of the dominant forms of UH that takes place in the United Kingdom. 163 volunteers in England and Wales participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…As discussed, many people may have avoided parks due to overcrowding and the associated risks of contracting SARS-CoV-2. However, allotments have provided an important community space during COVID-19 [ 65 ] and may provide a multiplicity of wellbeing benefits [ 66 ]. Further research focusing on the typology and quality of green spaces and their relationships with mental wellbeing is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, many people may have avoided parks due to overcrowding and the associated risks of contracting SARS-CoV-2. However, allotments have provided an important community space during COVID-19 [ 65 ] and may provide a multiplicity of wellbeing benefits [ 66 ]. Further research focusing on the typology and quality of green spaces and their relationships with mental wellbeing is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A suite of data available to practitioners and policy makers that takes into account the resource needs of different forms of UH, including commercial ventures that may need more costly environmental inputs, would be an invaluable tool to help site the most appropriate UH type in each available food growing space within a city. Previous research has demonstrated that allotment gardeners often share surplus produce with friends and family [65]; future research analysing the end location of harvests could bring an assessment of food miles into the picture of resource use sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Such projects have the potential to bring improvements in food security and food sovereignty to urban areas, whilst also increasing the engagement of citizens, local government and researchers in urban growing. Such collaborative projects highlight that with the right support, positive health community and environmental benefits can accrue (Beilin and Hunter, 2011;Dobson et al, 2020), as reported in the wider "urban food growing" literature (reviewed in Edmondson et al (2020)).…”
Section: Example 2 Urban Growingmentioning
confidence: 97%